Socialization of Role of LPM in Sustainable Village Development in Satra Village Klungkung Regency - Dewa Gede Pradnya Yustiawan; I.P. R. A. Putra; I. D. G. D. Sugama (Fakultas Hukum, Universitas Warmadewa, 2020)
This study aims to analyze the role of Community Empowerment Institutions (LPM) in supporting development that is not optimal. This study uses normative legal method with the aim of outlining the problem for further discussion based on legal theory. Then, the data were analyzed descriptively. The results of this study show that the Satra Village Community, Klungkung District, Klungkung Regency, generally do not understand the duties, functions and authority of the LPM including its existence as a work partner of the village head. Community understanding, village officials and LPM management are still not optimally related to work programs and positions as partners of village heads in implementing and planning development in the short, medium and long term. Thus, the existence of the LPM is currently limited to completing the organizational structure in the village administration and does not know the purpose why it was formed, what are its duties and authorities as village apparatus partner, thus, this condition can be ensured there is a gap between LPM and other organisation in the village administration, which until now has not been regulated even there are no regulations that explicitly regulate the benefits as LPM administrators. This caused many LPM officials who did not appear to be enthusiastic about managing LPM.